Strategi Komunikasi Pemasaran PT. Triloka Cahaya Prima Dalam Meningkatkan Brand Loyalty Melalui Instagram @Oxcart.Room - Yasmine Dhea Shafira; Asriyani Sagiyanto; Fajar Diah Astuti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to investigate and assess the marketing communication approach carried out by PT Triloka Cahaya Prima in strengthening brand loyalty through the Instagram account @oxcart. room. The main focus of this study is on the use of digital-based marketing strategies, especially the Pull, Push, and Pass approaches. The method applied in this study is qualitative with data collection techniques through in-depth interviews, participant observation, and documentation. Data analysis was carried out using the interactive analysis model by Miles and Huberman. The findings of this study indicate that the Pull strategy is utilized to create emotional attachment with the audience through visual content that tells stories, which depicts the production process, team activities, and consumer experiences. The Push strategy is realized by conveying technical information about screen printing and fabric products directly and in detail to encourage purchasing decisions. Meanwhile, the Pass strategy emphasizes social and local values through collaboration with creative communities and local brands such as @berkah. scotter. These three approaches are implemented in an integrated manner and build strong communication synergy, not only in attracting customer attention, but also in building trust, emotional closeness, and brand social image that contributes to increasing brand loyalty in a sustainable manner.